O Imposto sobre a Propriedade de Veículos Automotores paulista: um estudo sobre o domicílio tributário - Bernardi, Renato (2009)
Minimum lines have been dedicated to tax on the property of automobiles. The small quantity of material related may have its origin on the low representativeness of this tax in the general mounting of tax revenues of a Member State. All over the years, the tax over circulation of merchandises has called the attention of researchers, scholars and legislators, because it raises more questions and because of its great economic reflection in the public revenues and in the taxpayer budget. For the other side, tax on the property of automobiles in the State of São Paulo has raised debates and it has even been object of discussion in the internet. Based on article 155, Clause III, of the Brazilian Constitution, each Member State and the Federal District, by their legislative power, have created their tax on the property of automobiles. Therefore, in Brazil there are twenty seven state laws concerning tax on the property of automobiles. Because of the different tributary and fiscal politics, the state laws are divergent and raise conflicts related to the tributary war. Nowadays, the diverging topic that raises discussion is the different rates applied by each State Member. The existence of different rates gives the taxpayer the false idea that he may register his vehicle in the Member State he chooses, taking into consideration the value of the tax to be paid. The idea is false for various reasons that will be studied in the present work. There are practical, logical, legal and constitutional reasons that prevent the owner of a vehicle to choose the State Member to register his automobile. Without the intention of exhaust the subject, the present work intends to study the rules for the matter, concluding that there is no faculty in the choice of the tax domicile for tax on the property of automobiles